Phylogenetic analysis, morphological studies, element profiling, and muscarine detection reveal a new toxic Inosperma (Inocybaceae, Agaricales) species from tropical China - Zhou, Yu-Ling; Deng, Lun-Sha; Yang, Shu-Dong; Liu, Chao-Feng; Fan, Yu-Guang; Yu, Wen-Jie (Frontiers in Microbiology, 2023)
Tropical Asian collections of Inosperma are usually poisonous mushrooms that have caused many poisoning incidents. However, the species diversity and the toxic mechanism of these Inosperma species are still unclear. Here, we describe the discovery of Inosperma wuzhishanense sp. nov. from Wuzhishan City, Hainan Province, tropical China, the new species was identified based on morphological and multi-locus (ITS, nrLSU, and RPB2) phylogenetic analyses. The new species is characterized by its reddish-brown pileus, fibrillose stipes with finely protruding fibrils, rather crowded lamellae, smooth and ellipsoid basidiospores, and mostly clavate, thin-walled cheilocystidia.The new species is phylogenetically nested in the Old World tropical clade 2, and is sister to the tropical Indian taxa I. akirnum. Detailed descriptions, color photos of the new species, and the comparisons with its closely related species are provided. Additionally, the muscarine content of the new species was analyzed by ultraperformance liquid chromatography / tandem mass spectrometry (UPLC-MS/MS). The muscarine contents ranged from 4,359.79 ± 83.87 mg/kg to 7,114.03 ± 76.55 mg/kg, 2,748.37 ±•106.85 mg/kg to 4,491.35 ±•467.21 mg/kg, and 2,301.36 ± 83.52 mg/kg to 2,775.90 ± 205.624 mg/kg in the stipe, pileus, and lamellae, respectively. The elemental composition and concentration were determined using inductively coupled plasma-mass spectrometry (ICP-MS).A total of 24 elements were detected. Among the heavy metals detected, arsenic showed the highest level of toxicity with a concentration of 36.76 ± 0.43 mg/kg.